The inverse relationship between dietary anthocyanidins consumption and frailty: Findings from the National Health and Nutrition Examination Survey. - Xiaofeng Zhang; Pengpeng Huang; Zhenhua Jin; Yanfei Wu (PLoS ONE)
Objective This study investigates the association between dietary anthocyanidins consumption and the risk of frailty in the general adult population using data from the National Health and Nutrition Examination Survey (NHANES). Methods A cross-sectional analysis of NHANES data was conducted, examining the relationship between dietary anthocyanidins intake and frailty risk. Dose-response relationships and subgroup analyses were performed to provide a comprehensive understanding of the associations. Results The results indicate a significant inverse relationship between the consumption of specific anthocyanidin types, including malvidin and delphinidin, as well as total anthocyanidins, and the odds of frailty. Particularly, individuals aged 41-60 years and males exhibited a notable protective effect of anthocyanidins against frailty. Dose-response analyses revealed a U-shaped relationship between total anthocyanidins intake and frailty risk, with an optimal consumption level of 33.322 mg per day. Conclusion This pioneering study emphasizes the potential protective role of dietary anthocyanidins in mitigating frailty, especially among middle-aged individuals and males.